Four Ways to Achieve Freedom. About the Heroes of Russian Literature - Szczukin, Wasilij (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2023)
This article contains criticism of the neoliberal concept of positive freedom. The author offers his understanding of the ideal of freedom, which is based not on economic, but on social and psychological criteria. The Hegelian understanding of freedom as a conscious necessity, according to the author, is unacceptable for modern man. It is difficult not to agree with Dostoevsky’s opinion that it is not the choice of benefit and goodness, but the obligatory nature of this choice that deprives a person of that incomparable sense of freedom (Notes from the Underground). Not only the holy spirit, but also the human spirit, blows wherever it wants, and not only where it is “necessary” or prescribed to blow. It is also impossible not to take into account the possibility of the spontaneous launch of unpredictable mechanisms of nature and culture, which Yuri Lotman wrote about in Unpredictable Mechanisms of Culture (1993). The author of the article identifies four types of positive freedom, which are expressed in the images of some heroes of Russian literature. These include skete life, described in the writings of Nil Sorsky and other Russian hesychasts, Karamazovism, Oblomovism, and, finally, “secret” spiritual freedom. The author expresses sympathy for the latter concept of positive freedom, incompatible with both anarchic tyranny and “blessed” passivity.